Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/jnnp-2018-318060
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of low frequency stimulation of STN on dysphagia, freezing of gait and other motor symptoms in PD

Abstract: NCT02549859; Pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 39 publications
(22 reference statements)
0
50
0
2
Order By: Relevance
“…LFS (most commonly 60 Hz) STN-DBS has been tried to treat PD patients with FOG and have shown its shortterm or even long-term beneficial effects on improving FOG and other axial symptoms compared with HFS [133][134][135], although some studies argued that there was no significant difference between HFS and LFS for controlling FOG [136,137]. Currently, there are lack of metaanalysis to examine efficiency of low frequency STN-DBS on FOG, thus caution should be used in interpreting the results of these clinical studies and drawing conclusions.…”
Section: Stn-dbs Low Frequency Stimulation (Lfs)mentioning
confidence: 99%
“…LFS (most commonly 60 Hz) STN-DBS has been tried to treat PD patients with FOG and have shown its shortterm or even long-term beneficial effects on improving FOG and other axial symptoms compared with HFS [133][134][135], although some studies argued that there was no significant difference between HFS and LFS for controlling FOG [136,137]. Currently, there are lack of metaanalysis to examine efficiency of low frequency STN-DBS on FOG, thus caution should be used in interpreting the results of these clinical studies and drawing conclusions.…”
Section: Stn-dbs Low Frequency Stimulation (Lfs)mentioning
confidence: 99%
“…A limitation of the present study was the omission of repeat whole UPDRS-III in each condition; this would have enabled assessment of whether improvements in speech intelligibility achieved with LFS were to the detriment of benefits to other (axial) motor symptoms, especially swallowing. Recent studies have shown that low frequency (60 Hz) stimulation has a good effect on reducing aspiration frequency, perceived swallowing difficulty, freezing of gait severity, bradykinesia and overall axial and motor symptoms, although the overall effect decreases over time [47,48]. This would be challenging however in view of patient fatigue.…”
Section: Limitations Of the Study And Future Researchmentioning
confidence: 99%
“…Low-frequency STN-DBS and GPi-DBS (below 100 Hz) have shown encouraging beneficial effects on axial symptoms in PD; however, higher levels of evidence with randomized and blinded studies are needed to confirm the benefits [15]. Also, the overall benefits of low-frequency STN-DBS decrease with long-term use [16].…”
Section: Introductionmentioning
confidence: 99%